1974
DOI: 10.1901/jaba.1974.7-199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self‐recording on Attendance and Performance in a Competitive Swimming Training Environment

Abstract: Swimmers' attendance at training and work rates were described by their coaches as being poor and irregular. Reinforcement contingencies were developed to remedy these unsatisfactory conditions. Two experiments were conducted. A multiple baseline design verified the effects of publicly marking attendance at practice as a sufficient solution for reducing absenteeism, tardiness, and leaving early. Follow-up analyses showed this contingency to have lasting effects. In the second experiment, a reversal design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
51
1
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 9 publications
4
51
1
1
Order By: Relevance
“…One technique that has been successful in producing changes in other areas is public posting of performance. For example, public posting has been successfully used to improve the performance of psychiatric aides and attendants (Panyan, Boozer, & Morris, 1970;Pomerleau, Bobrove, & Smith, 1973;Quilitch, 1975), swimmers (McKenzie & Rushall, 1974), tutors (Barnard, Christophersen, & Wolf, 1974), and elementary school children (Van Houten, Hill, & Parsons, 1975;Van Houten, Morrison, Jarvis, & McDonald, 1974;Van Houten & Van Houten, 1977). The purpose of the present experiment is to determine whether public posting of driver performance can reduce speeding in a residential area.…”
mentioning
confidence: 99%
“…One technique that has been successful in producing changes in other areas is public posting of performance. For example, public posting has been successfully used to improve the performance of psychiatric aides and attendants (Panyan, Boozer, & Morris, 1970;Pomerleau, Bobrove, & Smith, 1973;Quilitch, 1975), swimmers (McKenzie & Rushall, 1974), tutors (Barnard, Christophersen, & Wolf, 1974), and elementary school children (Van Houten, Hill, & Parsons, 1975;Van Houten, Morrison, Jarvis, & McDonald, 1974;Van Houten & Van Houten, 1977). The purpose of the present experiment is to determine whether public posting of driver performance can reduce speeding in a residential area.…”
mentioning
confidence: 99%
“…Thus far, however, there have been few applications of the operant model to sports.1 For example, in swimming, reinforcement has been used to increase attendance at practice and increase number of laps swum by the individuals involved each day (McKenzie and Rushall, 1974;Rushall & Pettinger, 1969). The procedures included written instructions and self-recording on "program boards" with opportunities for social reinforcement such as attention and praise from coaches and peers.…”
mentioning
confidence: 99%
“…As an alternative it has been suggested that coaches focus more attention on the players' development and improvement, rather than on the eventual outcome of the game (Tutko and Richards, 1971 Rushall, 1973;Rushall and Siedentop, 1972), and have demonstrated the use of such techniques in studies involving competitive swimmers (McKenzie and Rushall, 1974;Rushall and Pittinger, 1969). With a behavioral approach, it might be possible to combine the competitive and the learning aspects.…”
mentioning
confidence: 99%